Green One Step Microwave Assisted Synthesis of ZnS Nanoparticles - Sabah, A.; Javed, S.; Nazir, M. (The Nucleus, 2015)
Microwave radiations are used to synthesize zinc sulphide (ZnS, cubic phase) nanoparticles by using single precursor at different synthesis temperature and irradiation time. Absorption peaks of ZnS nanoparticles of size 15 nm are found within the range of 250-320 nm by UV-Visible spectroscopy. The band gap energies of prepared ZnS nanoparticles are higher than the bulk value of ZnS. The blue shift of UV absorption peak gives evidence of decrease in particle size. Aggregates of large number of small sized spherical nanoparticles are observed by scanning electron microscope (SEM).